Remediation of groundwater contaminated with the lead–phenol binary system by granular dead anaerobic sludge-permeable reactive barrier. Issue 20 (18th October 2017) - Faisal, Ayad A. H.; Abd Ali, Ziad T.
ABSTRACT: Computer solutions (COMSOL) Multiphysics 3.5a software was used for simulating the one-dimensional equilibrium transport of the lead–phenol binary system including the sorption process through saturated sandy soil as the aquifer and granular dead anaerobic sludge (GDAS) as the permeable reactive barrier. Fourier-transform infrared spectroscopy analysis proved that the carboxylic and alcohol groups are responsible for the bio-sorption of lead onto GDAS, while phosphines, aromatic and alkane are the functional groups responsible for the bio-sorption of phenol. Batch tests have been performed to characterize the equilibrium sorption properties of the GDAS and sandy soil in lead and/or phenol containing aqueous solutions. Numerical and experimental results proved that the barrier plays a potential role in the restriction of the contaminant plume migration and there is a linear relationship between longevity and thickness of the barrier. A good agreement between these results was recognized with root mean squared error not exceeding 0.04.